Ácaros predadores como potenciais agentes de controle da mosca-branca-do-cajueiro - Alfaia, Josiane Pacheco de (2018)
The cashew whitefly, Aleurodicus cocois (Curtis 1846) (Hemiptera: Aleyrodidae), is considered one of the main plagues of the cashew tree however there are no products registered for its control. A possible alternative of their control is the use of predatory mites of the family Phytoseiidae, as control agents. In Europe and North America, phytoseiids Amblydromalus limonicus (Graman & McGregor), Amblyseius swirskii (Acari: Phytoseidae) and Euseius gallicus (Kreiter & Tixier) (Acari: Phytoseidae) have been used against another species of whitefly, to Bemisia tabaci (Gnnadius) (Hemiptera: Aleyrodidae). However, the potential of predatory mites against the cashew whitefly has not yet been evaluated. However, it is known that some species of predatory mites of the Phytoseiidae family occur naturally on leaves of the cashew tree, and some of these species may be efficient in controlling the cashew whitefly. The use of predatory mites could be one of the tools of the integrated management of this pest, whether through the conservation or release of these organisms. The objective of this work was to evaluate the potential for predation, development and reproduction of Amblyseius largoensis and Euseius concordis on Aleurodicus cocois, through functional response and biology experiments. The mites were evaluated in a laboratory at a temperature of 25 ± 1 ° C, Relative Humidity at 70 ± 10% and photoperiod of 12 h, fed with giant whitefly eggs collected from naturally infested cashew leaves. The mites tested showed potential for biological control of the giant whitefly, especially at low pest densities. The giant whitefly eggs provided the development of the two species tested. But the food did not favor the reproduction of Euseius concordis. Thus, Amblyseius largoensis is the most promising species for the control of the giant whitefly.